Simple method to gas cluster size determination based on molecular beam cross-section. (March 2016) - Korobeishchikov, N.G.; Penkov, O.I.
Abstract: A new experimental method of gas cluster size determination based on measuring the transverse profile of the total intensity of a molecular beam was developed. Since the supersonic beam has a high intensity, the proposed method not requires high-sensitivity detecting equipment. By using this method it can determine the mean cluster size in situ not only of any pure gases, but in gas mixtures under certain conditions as well. Experimental measurements were carried out in jets of pure gases (Ar, CO2, N2 ) and gas mixture (10% С2 Н4  + 90% Не) expansions through supersonic conical nozzles. The Hagena scaling parameter of the source conditions Г* varied from 10 2 to 2 × 10 4 . The mean cluster sizes defined by new method were in the range of 50–1500 molecules/cluster. Comparison of the experimental data to the results of numerical simulations and estimates using the empirical formulae developed elsewhere shows a satisfactory agreement. Highlights: New simple experimental method of gas cluster size determination is approved. Proposed method not requires high-sensitivity equipment. By new method it can determine the mean cluster size of any pure gases and some mixtures. Method was verified by compared with the results of simulation and empirical formulae.